Desain Ulang dan Analisis Logo pada Bisnis Penerbitan Kampus sebagai Identitas Perusahaan - Mayang Marshita; Vella Nabillah (Politeknik Negeri Batam, 2021)
Polibatam Press already has a visual identity in the form of a logo, but the Polibatam Press logo still does not have an identity that can describe the identity of the company. So far people know the existence of Polibatam Press only through word of mouth. Therefore, the company needs promotional media to introduce Polibatam Press. To be well known, Polibatam Press's identity requires a strong logo and Corporate Identity that is easy for people to remember. The logo design process was designed using the stages structure in making the logo. At the logo creation stage there are five steps in the logo design that will be carried out by the researcher in creating the visual identity desired by the client. At the testing stage of this study, the data analysis technique used is qualitative analysis. Sampling in this model uses snowball sampling technique. This testing model is used to get respondents' perception of a topic in accordance with the needs of researchers, the final result of this testing model is a conclusion, and an in-depth review, so that the visual identity displayed will make it easier for the public to recognize Polibatam Press.